Improvement of heat sink performance using paraffin/graphite/hydrogel phase change composite coating. (November 2022) - Paramparambath, Sreedevi; Maurya, Muni Raj; Houkan, Mohammad Talal; Cabibihan, John-John; Sadasivuni, Kishor Kumar
Abstract: Phase-change materials offer high latent heat and are widely used for energy storage applications. Paraffin wax is usually used as a phase-change material. However, its application in energy storage is restricted due to its low thermal conductivity. In the present work, graphite and graphite-hydrogel are used to enhance the thermal conductivity and heat release properties of paraffin wax. Wax-graphite (W-G) and wax-graphite-hydrogel (W-G-H) composites were synthesized by the dispersion of graphite and graphite-hydrogel in paraffin wax above its melting temperature. Scanning electron microscope (SEM) analysis was used to investigate the graphite and graphite-hydrogel distribution in the paraffin wax matrix. Thermogravimetric analysis (TGA) and differential scanning calorimeter (DSC) characterization were performed to measure the thermal stability and phase transition properties, respectively. DSC revealed that all composites have a similar melting temperature. The W-G-H composite displayed nearly 12 folds more thermal conductivity compared to the pure paraffin wax. High temperature brings adverse impacts on energy efficiency, and even destroys a semiconductor device. The synthesized W-G-H composite is proposed to decrease the working temperature of semiconductor devices. As an applicative demonstration, the W-G-H composite film was coated at the back of the solar panel. The W-G-H composite coated solar panel displayed a surface temperature that was near ∼4 °C lower than the bare solar panel while operating. The real-time experiment indicates that the W-G-H composite has high thermal conductivity and heat release properties. The study reports fundamentally new low-cost, simple, scalable, and self-adaptive, passive cooling technology to the semiconductor industry. The proposed material can further be developed in the form of paint and its heat sink properties can be improved by introducing hydrogels doped with Li + and Br − ions. Graphical abstract: Image 1 Highlights: Formulation of Paraffin Wax-Graphite-Hydrogel as a novel composite with enhanced properties. Thermal properties of composite PCM were measured and analyzed. The thermal conductivity of PCM composite is ∼12-fold higher than paraffin. Low-cost, simple, and scalable technology with applicability in passive cooling. Effective passive cooling of solar panels by PCM composite was validated.